NT-proBNP as a Predictor of Early Recovery in Elective Off-Pump CABG Patients - Samir Azam Sunny, Mohammad; Amirul Islam, Md.; Rahman, Ashiqur; Mozumder, Noor-E-Elahi; Alauddin, Md.; Amanur Rahman, Khan Mohammad (Journal of Neonatal Surgery, 2025)
Background: N-terminal pro–B-type natriuretic peptide (NT-proBNP) is a biomarker of myocardial stress and has been investigated for its prognostic utility in cardiac surgery. However, limited data exist on its role in predicting early recovery outcomes following elective off-pump coronary artery bypass grafting (OPCAB). This study aimed to evaluate the predictive value of preoperative NT-proBNP levels on postoperative recovery parameters in OPCAB patients. Methods: This prospective observational study was conducted at the Department of Cardiac Surgery, Al Helal Specialized Hospital, Dhaka, from June 2024 to January 2025. A total of 100 adult patients undergoing elective OPCAB were enrolled. Patients with preserved left ventricular function (LVEF ≥ 40%) were included, while those with prior cardiac surgery, emergency indications, severe renal impairment, or recent myocardial infarction were excluded. NT-proBNP levels were measured preoperatively and on postoperative days 1 and 3. Postoperative outcomes, including extubation time, ICU stay, inotrope requirement, and complications, were recorded and analyzed based on NT-proBNP quartiles. Results: The mean preoperative NT-proBNP level was 684 ± 310 pg/mL, which peaked at 1250 ± 430 pg/mL on postoperative day 1. Patients with higher preoperative NT-proBNP (>800 pg/mL) had significantly prolonged ICU stays (3.6 ± 1.4 days) and higher inotrope use (68%) compared to those with lower levels (<400 pg/mL), who had shorter ICU stays (2.1 ± 0.7 days) and less inotrope requirement (12%). Conclusion: Elevated preoperative NT-proBNP levels are associated with delayed recovery and increased hemodynamic support following OPCAB. NT-proBNP may serve as a valuable tool for early postoperative risk stratification.